An interdiscursive study of the founding texts of the Vaapostora veAfrica (African Apostolic) church of Paul Mwazha WeAfrica - Manyawu, Andrew T. (2016)
The exponential growth of Christianity on the African continent is, to a large extent, due to African Initiated Church (AIC) discourse's hybridity. Probably the most potent weapon in the strategy of African Apostolic Church of Zimbabwe archbishop, Paul Mwazha, is a founding text entitled “Kutumwa Kwa Paul Mwazha weAfrica” (English version: “The Divine Commissioning of Paul Mwazha of Africa”) Parts One and Two. This paper examines Part Two of Mwazha's text from a perspective of interdiscursivity in order to characterise its persuasive force. The study concludes that Mwazha's founding text incorporates a variety of voices, including the biography, the diary, the Bible and Bantu worldview. These discourses are skilfully used to contextualise Mwazha's voice. The choice of voices lends credibility to the author's voice through a judicious mix of styles related to Western, Biblical and Bantu discourses or worldviews.